Utilization of Reading Corners in the School Literacy Movement at the Mukhlisiin Gowa Integrated Islamic Elementary School - Nurhayati Nurhayati; Andi Sukri Syamsuri; Haslinda Haslinda (Buana Pendidikan, 2023)
This research aims to utilize reading corners, supporting factors and inhibiting the use of reading corners in the School Literacy Movement at Mukhlisiin Integrated Islamic Elementary School.  The approach used in this study was the cauldronative approach.  Research method to understand the phenomenon of experienced by the research subject.  This type of research used methods of interviewing, observation and document review. This research subject that consisted of 6 respondents from Mukhlisiin Integrated Islamic Elementary School. The data was analyzed using the Miles and Huberman models while the data validity test was performed by triangulation of sources and techniques. The results showed that the use of reading corners in the School Literacy Movement at Mukhlisiin Gowa Integrated Islamic Elementary School, among others: reading activities before learning, encouraged the students to tell about what they had read, providing books that made the students’ interest.  Meanwhile, the supportive  factors on the use of reading corners in Mukhlisiin Gowa Integrated Islamic Elementary School, among others:  the awareness of school residents on the importance of literacy culture, adequate physical fasilitas such as reading corners, the allocation of time to visit in the reading corner, reading by being dibimbing by teachers, parents partivcipation of learners. Some factors that can hinder the use of reading corners in the School Literacy Movement at Mukhlisiin Gowa Integrated Islamic Elementary School, among others: there was a special time for book reading activities in the classroom, furthermore the teachers could not accompany their students when the reading corner utilization activities, they did not hold book updates and the school had not supported the activities of utilizing reading corners well.